2021
DOI: 10.1111/vco.12687
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive ethyl cellulose ethanol ablation in domesticated cats with naturally occurring head and neck cancers: Six cats

Abstract: It is difficult to retain tumoricidal doses of ethanol in large or unencapsulated tumours without causing intoxication or damaging surrounding tissue. Ethyl cellulose‐ethanol ablation (ECEA) overcomes this limitation by trapping ethanol intratumorally. To evaluate the safety of ECEA and to develop a clinically feasible workflow, a single‐arm pilot study was performed in cats with lingual/sublingual squamous cell carcinoma (SCC). Six cats underwent intratumoral injection of 6% ethyl cellulose in ethanol. Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Injected ECE also exhibited decreased localized adverse events and increased overall survival in a syngeneic model of breast cancer, demonstrating the increased safety and efficacy of ECE in small animal models compared to ethanol alone [41]. Finally, injected ECE reduced tumor volume and was demonstrated as a feasible treatment for feline squamous cell carcinoma [42]. Overall, injected ECE ablation has the potential to address the need for a low-cost ablative therapeutic for the treatment of cancer in LMICs.…”
Section: Introductionmentioning
confidence: 90%
“…Injected ECE also exhibited decreased localized adverse events and increased overall survival in a syngeneic model of breast cancer, demonstrating the increased safety and efficacy of ECE in small animal models compared to ethanol alone [41]. Finally, injected ECE reduced tumor volume and was demonstrated as a feasible treatment for feline squamous cell carcinoma [42]. Overall, injected ECE ablation has the potential to address the need for a low-cost ablative therapeutic for the treatment of cancer in LMICs.…”
Section: Introductionmentioning
confidence: 90%
“…Controlling the diffusion of EtOH outside the ductal tree will be required to further minimize collateral tissue damage [101]. The use of ethyl cellulose as a gelling agent to limit ethanol diffusion has been reported for clinical treatment of venous malformation and in preclinical models of BC, cervical cancer, and liver cancer [152,[159][160][161][162][163][164][165]178]. We have shown that ethyl cellulose is compatible with a 70% EtOH ablative solution and with imaging contrast agents such as tantalum oxide nanoparticles in both mouse and rat models [152,153].…”
Section: Ductal Tree Ablationmentioning
confidence: 96%
“…Although tumor volume was reduced in some cats, concurrent lingual dysfunction occurred, excluding this kind of treatment from veterinary practice. However, further optimization of the applied treatment may make it an interesting minimally invasive option for curing oral, neck, and head cancers in cats and other animals [ 135 ]; Transdermal drug delivery—This involves drug delivery through the skin, and in veterinary medicine, it is a useful alternative to more traditional oral drug administration since it is non-invasive; avoids the gastric route, reducing potential gastric irritation and drug degradation; and has a reduced first-pass metabolism in the liver [ 134 , 136 ]. Cellulose and its derivatives can serve as a base for hydrogels with dispersed active ingredients, which perform better than creams and ointments due to their better adhesion, cooling effect, ease of removal, excellent drug-loading efficiency, and improved drug release.…”
Section: Application Of Biodegradable Polymers In Veterinary Medicinementioning
confidence: 99%
“…Transdermal drug delivery—This involves drug delivery through the skin, and in veterinary medicine, it is a useful alternative to more traditional oral drug administration since it is non-invasive; avoids the gastric route, reducing potential gastric irritation and drug degradation; and has a reduced first-pass metabolism in the liver [ 134 , 136 ]. Cellulose and its derivatives can serve as a base for hydrogels with dispersed active ingredients, which perform better than creams and ointments due to their better adhesion, cooling effect, ease of removal, excellent drug-loading efficiency, and improved drug release.…”
Section: Application Of Biodegradable Polymers In Veterinary Medicinementioning
confidence: 99%